Perbandingan Pelarut Etanol Dengan Etil Asetat Terhadap Aktivitas Antibakteri Ekstrak Kulit Buah Salak (Salacca Zalacca Reinw) Pada Pertumbuhan Bakteri Staphylococcus Aureus ATCC 25923 - Wahyuni, Umi Nurul; Sihotang, Yosua Maranatha; Marpaung, Mauritz Pandapotan; Prasetyo, Dani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Staphylococcus aureus is one of the most common bacteria causing infections in the world. One way to treat infections caused by S. aureus is by giving antibiotics. However, recently there have been many reports regarding antibiotic resistance. Efforts that can be made to deal with this resistance are using natural antibiotic ingredients, for example the skin of the zalacca (Salacca zalacca Reinw). This study aims to determine the difference between ethanol extract and ethyl acetate extract of the skin of zalacca (Salacca zalacca Reinw) against the antibacterial activity of Staphylococcus aureus. Salak fruit peel was extracted by maceration method using two solvents, namely ethanol and ethyl acetate. The extract obtained was then tested for antibacterial activity. The yield of the ethanol extract of the bark was higher, namely 1.57% compared to the ethyl acetate extract of 0.68%. The ethanol extract of the skin of the zalacca fruit has higher antibacterial activity than the ethyl acetate extract against Staphylococcua aureus bacteria.